Prevalence of Refractive Error and Strabismus in Primary School Children of Tehsil Lakki Marwat, Khyber Pakhtunkhwa Pakistan - Faheem Ullah; Naheed Mahsood; Waqas Mohyuddin; Saadullah Afridi; Zia ur Rehman (Gandhara University, 2020)
OBJECTIVES: Refractive errors and strabismus continue to remain a significant public health problem. Among school children it has an impact on child development. The aim of the study was to determine the prevalence and pattern of refractive error and strabismus among primary school children. METHODOLOGY: It was a cross-sectional study. Stratified random sampling technique was used to select the school children. Data was collected in November-December 2013. Visual impairment was defined as, presenting VA of < 6/12. A total of 2288 children (1746 boys and 542 girls) were screened from 26 randomly selected schools. Stratified sampling technique was used. Data were collected on pre-designed questionnaires and entered and analyzed by SPSS software version 16. RESULTS: The mean age of children was 8.10 + 2.3 years. About 4% children were found visually impaired. The prevalence of refractive error was found to be 5.4%, of which 88.6% was uncorrected refractive error. The prevalence of refractive error was found higher in girls than boys, 6.8% and 5.0% respectively. Among types of refractive error, myopia prevalence was 2.3%, hypermetropia prevalence was 2.0% and astigmatism prevalence was 1.1%. The prevalence of strabismus was 1.3%. Refractive error was found as a main cause of visual impairment in school children. Prevalence of strabismus among this study population is relatively low as compared to the global prevalence of 2% to 5%. CONCLUSION: It is recommended that more study to determine the extent of the problem and possible factors for development of refractive error and strabismus types are needed to mitigate these conditions.